Legal Problems of Sale with the Right of Redemption: A Case Study the Implementation of the People Protection Act in the Redemption of Agricultural Land or Residence Contracts, B.E. 2562 (A.D. 2019) - Vatcharakunphong, Nichsha; Thaboonma, Vayupak (Ph.D. in Social Sciences Journal, 2024)
This research article aims to study the concepts and legal principles of sale with the right of redemption in Thailand and abroad, legal problems of the redemption of agricultural land or residence contracts under the Civil and Commercial Code, and in the case of the People Protection Act in the Redemption of Agricultural Land or Residence Contracts, B.E. 2562 in order to obtain guidelines for solving such legal problems and related regulations that are clear, comprehensive, and of maximum benefit to the people.This research is a qualitative research and data collection is done through document research. Data analysis is done using content analysis technique. Findings are as follows: The legal problem of consignment contract is the differences between Civil and Commercial code and the People Protection Act in the Redemption of Agricultural Land or Residence Contracts, B.E. 2562. The Act requires a revision in some sections. The research showed various problems e.g. redemption determination, redemption periods, early redemption, rights of consignors, rights to redeem assets, consignment fee, and the form for redeeming extension. The solutions; for redeeming extension, requires to add official certificate of registration must be made in the presence of the authorized officer, for time frame of redemption extension correction, Section 10 paragraph 3 the rights to redeem by assets, Section 18 paragraph 2, redemption fee to the fee for consignment and redemption should be equal pay or the can consent to other assets.